Report of the Indian Productivity Delegation to Japan (Report and Appendices) - Ministry of Commerce and Industry Government of India (My University, 1957)
The Indian Productivity Delegation Report to Japan, prepared by the Ministry of Commerce and Industry, Government of India, presents a comprehensive examination of Japan’s remarkable post-war industrial resurgence and productivity movement, alongside detailed analyses of Japan’s economic development strategies, management practices, regional productivity institutions, and sectoral performance—particularly in the textile industry. The delegation observed that Japan’s rapid reconstruction following World War II was not solely attributable to technological advancement but was deeply rooted in effective organizational structures, merit-based professional management, cooperative labor-management relations, and coordinated government-industry collaboration. Central to this transformation was the Japan Productivity Centre and its Regional Centers, which fostered productivity awareness through research, training, technical exchange, and inclusive participation of management, labor, and academia. The report highlights Japan’s Five-Year Economic Self-Support Plan, emphasizing industrial expansion, export growth, technological modernization, small enterprise support, fiscal discipline, and social welfare objectives. Particular attention is given to the cotton textile industry, whose production, labor expansion, export growth, and gradual shift toward synthetic fibers illustrate Japan’s strategic adaptation to global market demands. The governance and financial frameworks of productivity institutions further demonstrate structured accountability and diversified funding sources, including government subsidies and international support. The delegation concludes that while institutional models cannot be transplanted wholesale, India can adapt Japan’s principles—systematic research integration, standardized production, participatory labor relations, and professionalized management—to strengthen its own productivity movement, especially in alignment with national planning objectives. Ultimately, the report serves as a strategic blueprint advocating philosophical as well as structural reforms to elevate industrial efficiency, competitiveness, and balanced economic development in India.
Ministry of Commerce and Industry Government of India
Ministry of Commerce and Industry Government of India
Keywords: Indian Productivity Delegation; Japan Productivity Centre; Economic Self-Support Plan; Five-Year Economic Plan; Industrial Productivity; Labor-Management Relations; Regional Productivity Centers; Textile Industry Development; Management Practices in Japan; Small Enterprise Support; Government-Industry Collaboration; Post-War Economic Reconstruction